Effect of microbial inoculants on the fermentation characteristics, nutritive value, and in vitro digestibility of various forages. (6th December 2018) - Wang, Siran; Li, Junfeng; Dong, Zhihao; Chen, Lei; Shao, Tao
Abstract: This study was aimed to examine the characteristics of three isolated lactic acid bacteria (LAB) strains (HG24, M1, and TG1), and to evaluate their effects on fermentation characteristics, nutritive value, and in vitro digestibility in a variety of substrates. The experiments were conducted with Italian ryegrass ( Lolium multiflorum Lam.), tall fescue ( Festuca arundinacea Schred.), and oat ( Avena sativa L.) in laboratory silo (1 L) for ensiling 30 days. All the treated silages had significantly ( p < 0.05) higher in vitro dry matter digestibility (IVDMD), and lower undesirable microorganism populations compared with controls. In Italian ryegrass and oat silages, all the inoculants improved the fermentation quality, evidenced by distinctly ( p < 0.05) higher LA contents and ratios of LA to acetic acid, and lower pH, butyric acid and ammonia nitrogen contents. Strains HG24 and commercial inoculant G ( Lactobacillus plantarum MTD‐1) performed better than strains M1 and TG1, indicated by obviously ( p < 0.05) higher LA contents, LAB numbers, and IVDMD. In tall fescue silage, all the isolated LAB strains (HG24, M1 and TG1) markedly ( p < 0.05) increased IVDMD compared with strain G. Strain HG24 is recommended as a good LAB inoculant for ensiling in various forages.